Association between in-hospital hemoglobin drop without overt bleeding and 1-year outcome of percutaneous coronary intervention in acute myocardial infarction patients - He Zhou; Miaohan Qiu; Shaoyi Guan; Zhenyang Liang; Yi Li; Yaling Han (Scientific Reports)
Abstract Whether an in-hospital hemoglobin drop adversely affects the prognosis of patients with acute myocardial infarction (AMI) remains controversial. The present study aimed to investigate the impacts of in-hospital hemoglobin drop without overt bleeding on 1-year clinical outcomes of AMI patients after percutaneous coronary intervention (PCI). A total of 5,036 AMI patients who underwent PCI and presented with an in-hospital hemoglobin decline without overt bleeding were recruited in this study. Subsequently, these patients were stratified into three cohorts based on tertiles of hemoglobin drop values: < 0.8 g/dL (n = 1652), 0.8–1.49 g/dL (n = 1651) and ≥ 1.5 g/dL (n = 1733). The primary endpoint was defined as ischemic events at 1 year, composed of cardiac death, myocardial infarction (MI), and stroke. Secondary endpoints were defined as 1-year all-cause death, Bleeding Academic Research Consortium (BARC) types 2, 3, or 5, and 3 or 5 bleeding. There were significant differences in 1-year incidence of ischemic events (1.88% vs. 3.27% vs. 3.46%; P = 0.0114), all-cause death (1.45% vs. 2.18% vs. 2.94%; P = 0.0128), as well as cardiac death (1.15% vs. 1.82% vs. 2.37%; P = 0.0282) and MI (0.30% vs. 1.15% vs. 0.92%; P = 0.0175) across tertiles of hemoglobin drop values. For each 1 g/dL drop in hemoglobin values, the adjusted risk for ischemic events and all-cause death increased by 2% and 3%, respectively. Among AMI patients undergoing PCI, an in-hospital decline in hemoglobin levels was associated with an increased risk of 1-year ischemic events and all-cause death, even in the absence of overt bleeding.